17β-estradiol modifies human spermatozoa mitochondrial function in vitro. Issue 1 (December 2016) - Kotwicka, Malgorzata; Skibinska, Izabela; Jendraszak, Magdalena; Jedrzejczak, Piotr
Abstract Background It is assumed that spermatozoa are target cells for estrogens however, the mechanism of their action is not fully understood. The aim of this study was to investigate the influence of 17β-estradiol (E2) on the human spermatozoa mitochondrial function. Methods The effects on spermatozoa of E2 at final concentrations of 10−10, 10−8 and 10−6 M were studied regarding the following phenomena: (1) kinetics of intracellular free calcium ions changes (using Fluo-3), (2) mitochondrial membrane potential ΔΨm (using JC-1 fluorochrome), (3) production of superoxide anion in mitochondria (using MitoSOX RED dye), (4) spermatozoa vitality (propidium iodide staining) and (5) phosphatidylserine membrane translocation (staining with annexin V marked with fluorescein). Results E2 initiated rapid (within a few seconds) dose dependent increase of intracellular free calcium ions concentration. E2 was changing the mitochondrial membrane potential: 10−8 M initiated significant increase of percentage of high ΔΨm spermatozoa while the 10−6 M induced significant decrease of high ΔΨm cells. In spermatozoa stimulated with E2 10−6 M a significant increase of mitochondrial superoxide anion level was observed. 2 h incubation of spermatozoa with E2 did not alter cells vitality nor stimulated phosphatidylserine membrane translocation, for all three doses. Conclusions 17β-estradiol affected the human spermatozoa mitochondrial function. E2 in low concentration improved while in high concentration might deteriorate mitochondrial function.